Metodologi Penemuan dan Pengembangan Hukum Islam - Hamka Husein Hasibuan; Faisar Ananda; Muhammad Syukri Albani Nasution (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This article examines the methodology of discovering and developing Islamic law, starting from the premise that Islamic law has two dimensions: divine law on the one hand, and human-made law on the other. The relationship between text (nash), reason, and social reality is mapped into two paradigms, namely the structural paradigm, which places text as the dominant structure, and the functional paradigm, which emphasizes dynamic and diait dsignificanceetween the three entities. This article shows that the methodology of legal discovery in the ushul al-fiqh tradition (bayānī, ta‘līlī, and istiṣlāḥī) is generally rooted in the structural paradigm, with naṣh as the main normative (structural) source. This paradigm experienced a crisis when confronted with modern social reality. It is in this context that a model of Islamic legal reform emerged, moving within a functional paradigm. This reform is articulated in two forms. First, religious utilitarianism, which focuses on the development of lawad on maslahah thenstudy'sasid al-shariah. Second, religious liberalism, which emphasizes rationality, social context, and ethical-historical dimensions in the reading of texts. Neither of these two schools of thought negates the authority of the text, but rather presents a productive dialectic model between revelation, reason, and reality, in order to produce more responsive laws.